Challenges faced in developing an ideal chronic wound model. (2nd January 2023) - Tan, Mandy Li Ling; Chin, Jiah Shin; Madden, Leigh; Becker, David L.
ABSTRACT: Introduction: Chronic wounds are a major drain on healthcare resources and can lead to substantial reductions in quality of life for those affected. Moreover, they often precede serious events such as limb amputations and premature death. In the long run, this burden is likely to escalate with an ageing population and lifestyle diseases such as obesity. Thus far, the identification of beneficial therapeutics against chronic wounds have been hindered by the lack of an ideal chronic wound animal model. Although animal models of delayed healing have been developed, none of these models fully recapitulate the complexity of the human chronic wound condition. Furthermore, most animals do not develop chronic wounds. Only the thoroughbred racehorse develops chronic ulcers. Areas covered: In this review, the different characteristics of chronic wounds that highlight its complexity are described. In addition, currently available models reflecting different aspects of chronic wound pathology and their relevance to human chronic wounds are discussed. This article concludes by listing relevant features representative of an ideal chronic wound model. Additionally, alternative approaches for the development of chronic wound models are discussed. Expert opinion: Delayed models of healing, including the streptozotocin diabetic model, skin flap model and magnet-induced IR models have emerged. While these models have been widely adopted for preclinical therapeutic testing, their relevance towards human chronic wounds remains debatable. In particular, current delayed healing models often fail to fully incorporate the key characteristics of chronic ulcers. Ultimately, more representative models are required to expedite the advancement of novel therapeutics to the clinic.